Analisis Pembelajaran Think Pair Share Untuk Menumbuhkan Kemampuan Berpikir Kritis Siswa sekolah dasar: Analisis Efektivitas Think Pair Share terhadap Kemampuan Berpikir Kritis - Atika Okta Rina; Mega Kusuma Putri; Hetilaniar Hetilaniar (Study program PGSD FKIP Universitas Bung Hatta, 2026)
The limited critical thinking abilities of elementary school students are frequently caused by the prevalence of traditional teacher-centered teaching approaches and the absence of significant interaction among students. This research seeks to thoroughly and comprehensively examine the role and application methods of the Think Pair Share (TPS) cooperative learning model in enhancing the critical thhinking abilities of elementary school students. The method of research employed is library research utilizing a qualitative approach, wherein data is gathered from diverse reputable academic sources and subsequently analyzed thematically. The conceptual framework employed in examining this phenomenon pertains to Jean Piaget's Cognitve Development Theory and Lev Vygotsky's Social Constructivism Theory. The analysis results indicate that every phase in the TPS syntax can consistently affect children's critical thinking indicators. The think stage successfully cultivates cognitive autonomy and preliminary analysis by allowing for wait time. The pair stage enables the assessment, clarification, and negotiation of arguments through peer tutoring in a controlled and secure environment. Simultaneously, the shared stage enhances students' reflective communication abilities, improved interpretation, and self-management in a public setting. TPS is a strategic and flexible teaching approach aimed at improving children's critical thinking, given that educators can create challenging problems and effectively handle classroom interactions inclusively.